Dynamic imaging of pancreatic diseases by contrast enhanced coded phase inversion harmonic ultrasonography. Issue 6 (11th May 2004) - Kitano, M; Kudo, M; Maekawa, K; Suetomi, Y; Sakamoto, H; Fukuta, N; Nakaoka, R; Kawasaki, T
Abstract : Background: Coded phase inversion harmonic ultrasonography, a newly available sonographic technique, enables visualisation of slow flow in minute vessels in a real time fashion with the use of a sonographic contrast agent containing monosaccharide. Our purpose was to employ this novel technique to observe microvessels in pancreatic tumours. Subjects and methods: Sixty five patients with suspicious pancreatic tumours received contrast enhanced coded phase inversion harmonic ultrasonography, contrast enhanced computed tomography, and endosonography. Final diagnoses based on histological findings were pancreatic ductal carcinomas in 49 patients, inflammatory pseudotumours with chronic pancreatitis in seven, and endocrine tumours in nine. For contrast enhanced coded harmonic ultrasonography, Levovist, a contrast agent, was injected intravenously as a bolus. When the first microbubble signal appeared in the pancreas, images of the ideal scanning plane were displayed in a real time continuous fashion (vessel images). Subsequently, interval delay scanning (perfusion images) was taken to demonstrate parenchymal flow. Tumour vascularity was evaluated by using the two types of imaging. Sensitivities for depicting pancreatic tumours were compared between three examinations. Results: Contrast enhanced ultrasonography demonstrated tumour vessels in 67% of pancreatic ductal carcinomas, although most were relatively hypovascular compared with the surrounding pancreatic tissue. The vascular patterns of tumours obtained by contrast enhanced ultrasonography were closely correlated with those obtained by contrast enhanced computed tomography. Values for sensitivity in depicting pancreatic tumours of 2 cm or less in size were 68% for contrast enhanced computed tomography, 95% for endosonography, and 95% for contrast enhanced ultrasonography. Conclusion: Contrast enhanced coded phase inversion harmonic ultrasonography successfully visualised fine vessels in pancreatic tumours and may play a pivotal role in the depiction and differential diagnosis of pancreatic tumours.